Cooperation between the EU and Central Asia countries in the education field. - Zairova, Kamilya (2022)
This master’s thesis describes the process of building consistent relationship in terms of education cooperation between two regions: European Union and Central Asia, both actors are interested in further developing of bilateral relations what shown in the list of Agreements and adopted documents of European Commission, National Offices of Programs Erasmus+ and Tempus. Starting from the aspiration of Central Asian countries to be included in Bologna Process in 1999 till present days’ sharing experiences and knowledge travel through the world effectively. Using the method of original empirical study with conducted qualitative, quantitative and mixed research. Thanks to gathered opinions of the conducted research – the survey and the interviews – the author was able to work with primary data from students and their insights were implemented in testing the efficiency of existing programs. In conclusion the benefits of long-term cooperation were estimated, and fruits of this cooperation is analyzed.